Governance Reform in Indonesia and Korea (UGM Press, 2011)
This book has been prepared in an attempt to systematically structure pieces of experiences from both Indonesian and Korean’s scholars who deeply delve on governance reform. This is a priceless effort as the book could facilitate both practitioners and academicians to gain knowledge on how each country has performed the governance reform. All chapters in this book are based on the belief that the important dimensions of any analysis of governance reform are that it be comparative. It is important to give us a chance to look at one’s system in a more objective way. However, this work cannot claim to be a fully comparative analysis between Indonesia and Korea. The co-authors do not make any general theoretical claim concerning the differences and the similarities in the system of governance reform in both countries. As a comparative perspective, the chapters in this book are, however, structured to make it possible to show how both countries continue in attempting to find better ways of governance reform. We cannot change the history, but we are writing a new history every day. We may not be able to change the bureaucratic culture in a week, but the culture is determined by society’s accumulated response to the governance system of a country.